Autocontenção no judiciário brasileiro : fatores que possibilitam a ocorrência do fenômeno em sede de arguição de descumprimento de preceito fundamental - Pontes, Juliana de Brito Giovanetti (2013)
The constitutionality control aims to maintain the unity of the legal system and the structures that constitute the state. When the balance of the legal system is altered, is through the use of constitutional control that are sourced means of correcting for this imbalance to harmonize the infraconstitucional law or normative act and the Constitution. From the 1988 Constitution, the arguição de descumprimento de preceito fundamental marked an advance in the Brazilian control of constitutionality. Institute unique in the world, is able to prevent acts of threat or breach of fundamental precept deriving from the Government. Is a means of concentrated constitutionality control, being exclusive and original jurisdiction of the Brazilian Supreme Court. By being inserted in the context of the judicialization of politics and judicial activism, in the judgment of the ações diretas de inconstitucionalidade, as compared to other forms of concentrated constitutionality control, is possible to check a small quantitative of pleas effectively judged and may result in losses to the achievement of the fundamental precepts. It is observed that as a result of the low level of decision-making processes in ADPFs, they have not always been recognized as a suitable means to resolve breaches the constitutional commandments, which causes the emptying of its importance in the concentrated constitutionality control. Due to this situation, this work seeks to analyze the existence of judicial self-restraint and what the factors have contributed to the practice of this phenomenon by the Brazilian Supreme Court in place of invoking a arguição de descumprimento de preceito fundamental. Therefore, through quantitative and qualitative analysis, we sought to understand the positive and negative selectivity in the judgment of pleas of breach made by the Supreme Court based on the analysis of the actions that have not been judged on the merits and the merits of those who had examined. It also was analyzed the behavior of Justices of the Supreme Court with regard to the requirement of subsidiarity and respect the Law 9.882/99, which regulates the ADPFs. The research included a literature review of doctrinal and jurisprudential references concerning the main concepts and theories that integrate this dissertation, also constituting a search for exploratory and descriptive, then monitoring the procedure of all ADPFs through electronic website of the Brazilian Supreme Court, proposals including the pleas in the period from December 1999 to July 2013, through the development of worksheet to the accompaniment of variables related of the complaints of breach and investigation of research hypotheses.